A miniature closed‐circle flow cell for high photon flux X‐ray scattering experiments. (29th September 2015) - Sahle, Ch. J.; Henriquet, C.; Schroer, M. A.; Juurinen, I.; Niskanen, J.; Krisch, M.
Abstract : A closed‐circle miniature flow cell for high X‐ray photon flux experiments on radiation‐sensitive liquid samples is presented. The compact cell is made from highly inert material and the flow is induced by a rotating magnetic stir bar, which acts as a centrifugal pump inside the cell. The cell is ideal for radiation‐sensitive yet precious or hazardous liquid samples, such as concentrated acids or bases. As a demonstration of the cell's capabilities, X‐ray Raman scattering spectroscopy data on the oxygen K ‐edge of liquid water under ambient conditions are presented.